Effective Relationship Engagement in the Post-Integration of Mergers and Acquisitions - Jedin, Mohd Haniff; Saad, Norsafinas Md (International Review of Management and Marketing, 2016)
Research on the relationship engagement in mergers and acquisitions (M&As) is still unclear although this phenomenon has been explored in the global multi-business environments. Furthermore, existing research does not clearly demonstrate the role of relationship among M&A players within the amalgamation processes between acquirer and the acquired firm. Hence, this paper addresses the factors that related to the relationship engagement among the M&A players particularly from the perspectives of Malaysian acquirers. This paper highlights four major indicators on effective relationship engagement: collaboration, face to face interaction, on-line communication and collegial relationships between the acquirer and the acquired firms. Drawing from the extant literature, hypotheses are developed, elaborating success factors to improve the M&A integration performance through relationship engagement initiatives. Keywords: Relationship Engagement, Mergers and Acquisitions JEL Classifications: C610, C623, I23